2019
DOI: 10.1097/mpg.0000000000002384
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Children With Chronic Intestinal Failure

Abstract: Background and Aims: The aim of the study was to aid decisions on prognosis and transplantation; this study describes the outcome of children with intestinal failure managed by the multidisciplinary intestinal rehabilitation program at the Royal Children's Hospital, Melbourne. Methods: Retrospective review of children requiring parenteral nutrition (PN) for >3 months who were assessed for home PN between 1991 and 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
1
13
0
2
Order By: Relevance
“…This observation is consistent with what has been described in the literature 8,18 . However, unlike previous studies, we did not find any association of BSIs with mortality 3,27 . This is, once again, reflective of improved care that prevents mortality but fails to negate the effect of BSIs on EA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with what has been described in the literature 8,18 . However, unlike previous studies, we did not find any association of BSIs with mortality 3,27 . This is, once again, reflective of improved care that prevents mortality but fails to negate the effect of BSIs on EA.…”
Section: Discussionsupporting
confidence: 92%
“…It is also important to note that IFALD was not predictive of EA or survival in our cohort. This is different from the majority of previous publications that have found IFALD to be predictive of mortality 8,10,26,27 . In their meta‐analysis of 201 studies on pediatric patients with IF (the vast majority of which were prior to the advent of FOLEs), Pierret et al found that catheter‐related BSIs and IFALD were the only two factors predictive of mortality for their patients 8 .…”
Section: Discussionmentioning
confidence: 73%
“…La eficacia del manejo entregado en UCE, se ve reflejada en 2 aspectos: El primero, y más importante, es el porcentaje de autonomía enteral al alta y, en segundo lugar, la disminución de la desnutrición al egreso. Respecto a la autonomía enteral, ésta se logró en un 66,7%, siendo comparable con el 56,9% de 15,20,22 . El grupo de pacientes que no lograron autonomía presentaban factores pronósticos desfavorables 20 : clasificación anatómica tipo I y II, ausencia de VIC, remanente intestinal < 40 cm y NM.…”
Section: Discussionunclassified
“…Respecto a la autonomía enteral, ésta se logró en un 66,7%, siendo comparable con el 56,9% de 15,20,22 . El grupo de pacientes que no lograron autonomía presentaban factores pronósticos desfavorables 20 : clasificación anatómica tipo I y II, ausencia de VIC, remanente intestinal < 40 cm y NM.…”
Section: Discussionunclassified
“…In the same work, the survival rate was 84% over 20 years in patients with chronic IF managed with long-term PN with reduced mortality related to the reduction in the volume of lipid administered and the use of FO-LEs. The authors found that IFALD was the main predictor of poor outcome, so that patients with severe and refractory IFALD represent the group in which intestinal transplantation may offer benefit ( 82 ). There is evidence about liver fibrosis regression after intestinal transplantation, probably due to the intestinal permeability and gut–liver axis improvement ( 29 ).…”
Section: Prevention and Treatmentmentioning
confidence: 99%